2010
DOI: 10.1103/physrevb.82.054437
|View full text |Cite
|
Sign up to set email alerts
|

Renormalization group study of the two-dimensional random transverse-field Ising model

Abstract: The infinite-disorder fixed point of the random transverse-field Ising model is expected to control the critical behavior of a large class of random quantum and stochastic systems having an order parameter with discrete symmetry. Here we study the model on the square lattice with a very efficient numerical implementation of the strong disorder renormalization group method, which makes us possible to treat finite samples of linear size up to L = 2048. We have calculated sample dependent pseudocritical points an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
158
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(185 citation statements)
references
References 52 publications
24
158
3
Order By: Relevance
“…One possibility is that the the model looks more and more disordered at larger length scales near criticality. This is the case for random transverse field Ising models in one and two dimensions 19,26,27 . In such cases, the model flows towards infinite randomness, and the strong disorder renormalization group becomes asymptotically exact near criticality 18 .…”
Section: Strong Disorder Renormalization Of the 2d Disordered Romentioning
confidence: 95%
See 1 more Smart Citation
“…One possibility is that the the model looks more and more disordered at larger length scales near criticality. This is the case for random transverse field Ising models in one and two dimensions 19,26,27 . In such cases, the model flows towards infinite randomness, and the strong disorder renormalization group becomes asymptotically exact near criticality 18 .…”
Section: Strong Disorder Renormalization Of the 2d Disordered Romentioning
confidence: 95%
“…For large clusters, the link decimation rule for addition of charging energies (26) implies that U ∼ s −1 , and therefore:…”
Section: Glassmentioning
confidence: 99%
“…As a final remark, we should stress the difference with the strong disorder renormalization method (see [51] for a review) that has been developed for disordered quantum short-ranged spin models either in d = 1 [52] or in d = 2, 3, 4 [53][54][55][56][57][58][59][60][61][62][63]. In these quantum spin models, the idea is to decimate the strongest coupling J max remaining in the whole system : the renormalized couplings obtained via second order perturbation theory of quantum mechanics are typically much weaker than the decimated coupling J max , so that the procedure is consistent and the typical renormalized couplings decays as J typ L ∝ e −L ψ .…”
Section: Ementioning
confidence: 99%
“…Spin glasses are the paradigmatic models of such theoretical challenge and, presumably, their phase transitions should govern by the IRFP [6]. Although recent theoretical works [7][8][9] support this conjecture, old Monte Carlo studies concluded that for two [10] and three [11] dimensions, the quantum phase transition of such systems is instead conventional (with z takes a finite value). Subsequent simulation research has explored this same problem concluding that in two dimensions and at the critical point, several observables (different versions of the Binder cumulant and the correlation length) do not follow a conventional dynamic scaling [12].…”
mentioning
confidence: 99%